Investigating Reading Challenges Faced by EFL Learners at Elementary Level - Raja Muhammad Ishtiaq Khan; Muhammad Shahbaz; Tribhuwan Kumar; Imran Khan (UIN Salatiga, 2020)
It is hard to ignore the importance of reading skills for desired proficiency in foreign languages. Reading can be beneficial for learners to immerse themselves in the target language and learn it efficiently. In EFL contexts like Saudi Arabia, learners face many challenges in reading skills. The main purpose of this research was to explore reading problems of elementary level students and causes of the readings skills inabilities. Following random and convenience sampling techniques; this mixed-method research obtained quantitative data from 290 elementary level students and qualitative data from nine teachers and supervisors. The analysis of quantitative data from the reading test and checklist and qualitative data retrieved from interviews suggests that students considerably perform relatively low in reading skills, and the main reasons are poor vocabulary, incorrect pronunciation, wrong spellings, slow reading pace, and flawed grammar. These five areas account for more than 90% of the challenges faced by learners in reading skills. Based on evidence from this research, we suggest that policymakers, teachers, and students should focus on these five areas for solving the issues related to reading skills. Although other avenues are essential, these items demand special attention to develop the reading skills of EFL learners in Saudi Arabia and elsewhere in the world.Keywords: Reading skill, Elementary level, Reading Pace, EFL